2014
DOI: 10.1016/j.ejphar.2013.10.052
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in rat aortic endothelial function of streptozotocin-induced diabetes: Possible involvement of superoxide and nitric oxide production

Abstract: Little is known of the interactions between diabetes and sex on vascular function. The objectives of this study were to investigate whether there were sex differences in rat aortic endothelial function one week after the induction of streptozotocin (STZ)-diabetes, and to examine the potential roles of superoxide and nitric oxide (NO) in this sex-specific effect. Endothelium-dependent vasodilatation to acetylcholine (ACh) was measured in rat aortic rings before and after treatment with MnTMPyP (25 μM), a supero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 46 publications
3
18
2
1
Order By: Relevance
“…In the current study, we observed a greater impairment of EDV to ACh as well as bradykinin (another endothelium-dependent vasodilator, data not shown) in rat aortic rings of female rats than males, 8 weeks following the induction of diabetes. However, when compared with the observations in the 1-week study (Han et al 2014), the effect of 8-week STZ-induced D r a f t diabetes in blunting EDV in females was much greater than in males as assessed by bigger rightward shift of ACh response compared to that in the 1-week study (Han et al 2014). This may suggest that the extent of EDV impairment in female diabetic rat aorta is dependent on the duration of the diabetic state among other factors.…”
Section: Discussioncontrasting
confidence: 53%
See 4 more Smart Citations
“…In the current study, we observed a greater impairment of EDV to ACh as well as bradykinin (another endothelium-dependent vasodilator, data not shown) in rat aortic rings of female rats than males, 8 weeks following the induction of diabetes. However, when compared with the observations in the 1-week study (Han et al 2014), the effect of 8-week STZ-induced D r a f t diabetes in blunting EDV in females was much greater than in males as assessed by bigger rightward shift of ACh response compared to that in the 1-week study (Han et al 2014). This may suggest that the extent of EDV impairment in female diabetic rat aorta is dependent on the duration of the diabetic state among other factors.…”
Section: Discussioncontrasting
confidence: 53%
“…It is also known that there are sex differences in NO bioavailability and that females have higher levels of NO than males (Forte et al 1998;GlushkovskayaSemyachkina et al 2006;Sullivan et al 2010). When compared NO-dependent responses in intact aortic rings, both enhanced (Aloysius et al 2012;Gisclard et al 1988;Rahimian et al 1997) or no change (Han et al 2014;Hayashi et al 1992 Shimizu et al 1993). In line with previous reports (Fukao et al 1997;Han et al 2014;Keegan et al 1995;Pieper and Siebeneich 1997;Shimizu et al 1993;Zhang et al 2012) demonstrate a compromised EDV in different vascular beds in diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations